The Mirror Constant of Glass Substrates by 4PB Test. Issue 1 (June 2014) - Lin, Mao‐Hsing; Pan, Wei‐Wu; Cheng, Po‐Jen; Huang, Kun‐Feng
Abstract Fractography is one of the methods to identify the condition that fracture occurred on brittle material, such as glass. There are several geometric characteristics on fracture surface, including mirror, mist, hackle, wallner lines, etc. to help to observe where the origin is and how much stress it suffered when broken. This study uses four‐point bending test to obtain the fracture stress on test specimens and performs fractographic analysis to find out the mirror constant on glass substrates in different manufacturing processes. This article makes the clues to track if the glass was broken, whereas provides the hints to improve the glass strength in further steps.